1997
DOI: 10.1046/j.1365-294x.1997.00238.x
|View full text |Cite
|
Sign up to set email alerts
|

Effective number of breeding adults in Bufo bufo estimated from age‐specific variation at minisatellite loci

Abstract: Estimates of the effective number of breeding adults were derived for three semi-isolated populations of the common toad Bufo bufo based on temporal (i.e. adult-progeny) variance in allele frequency for three highly polymorphic minisatellite loci. Estimates of spatial variance in allele frequency among populations and of age-specific measures of genetic variability are also described. Each population was characterized by a low effective adult breeding number (Nb) based on a large age-specific variance in minis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
87
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(94 citation statements)
references
References 54 publications
(36 reference statements)
7
87
0
Order By: Relevance
“…We estimated relatively low effective population sizes (N e ) in all of our breeding ponds, ranging from N e = 11 to 64. These estimates are similar to estimates of N e in other salamanders (Funk et al 1999;Jehle and Arntzen 2002;Savage et al 2010) and other amphibians (Scribner et al 1997;Driscoll 1999;Rowe and Beebee 2004;Wang 2009), all of which describe effective population sizes well below 100 individuals per population and often as small as N e = 10-20. Additionally, a recent review of estimates of N e across animal systems has indicated that effective population sizes in wild animal populations are generally smaller than previously thought (Frankham 2009).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We estimated relatively low effective population sizes (N e ) in all of our breeding ponds, ranging from N e = 11 to 64. These estimates are similar to estimates of N e in other salamanders (Funk et al 1999;Jehle and Arntzen 2002;Savage et al 2010) and other amphibians (Scribner et al 1997;Driscoll 1999;Rowe and Beebee 2004;Wang 2009), all of which describe effective population sizes well below 100 individuals per population and often as small as N e = 10-20. Additionally, a recent review of estimates of N e across animal systems has indicated that effective population sizes in wild animal populations are generally smaller than previously thought (Frankham 2009).…”
Section: Discussionsupporting
confidence: 82%
“…Effective population sizes (N e ) in wild animal systems vary widely (Scribner et al 1997;Crawford 2003;Hoffman et al 2004;Palstra and Rruzzante 2008) and determining N e for threatened and endangered species is a key component of their conservation and management (Andersen et al 2004;Rowe and Beebee 2004;Beebee 2005;Schwartz et al 2007). Reduced effective population sizes can lead to deleterious effects, including inbreeding depression and loss of genetic diversity, which can diminish the ability of a species or population to adapt to environmental change and to respond to risks from diseases and pathogens (Crnokrak and Roff 1999;Nieminen et al 2001;Keller et al 2002;Frankham 2005).…”
Section: Introductionmentioning
confidence: 99%
“…On the assumption that all islands started out with the same initial allele frequencies, Easteal estimated N e from current F ST and the number of generations that had passed since colonization, and found the ratio of effective to census sizes, N e /N c ഠ 0.001. This estimate is very low (Nunney 1992(Nunney , 1996, but is similar to a single-season estimate of N b /N c for toad populations in Europe (Scribner et al 1997). We do not know if these variable estimates represent a fundamental difference between bufonid toads and ranid frogs.…”
supporting
confidence: 82%
“…However, there could be consistent differences in N e :N c ratios between frog and toad populations. B. bufo has a very low N e :N c ratio (p0.01) based on genetic estimates that took account of variances in sex ratio and reproductive success, but not long-term fluctuations in population size over multiple generations (Scribner et al, 1997). Although no comparable studies have been reported for frogs, R. temporaria has a similar reproductive biology and seems unlikely to differ greatly from B. bufo in this respect.…”
Section: Discussionmentioning
confidence: 97%